Classification of gravitational waves in higher-dimensional space-time and possibility of observation - Yu-Qiang Liu; Yu-Qi Dong; Yu-Xiao Liu (European Physical Journal C: Particles and Fields, 2023)
Abstract The direct detection of gravitational waves opens the possibility to test general relativity and its alternatives in the strong field regime. Here we focus on the test of the existence of extra dimensions. The classification of gravitational waves in metric gravity theories according to their polarizations in higher-dimensional space-time and the possible observation of these polarizations in three-dimensional subspace are discussed in this work. We also show that the difference in the response of gravitational waves in detectors with and without extra dimensions can serve as evidence for the existence of extra dimensions.